Effect of silicon anodisation on aluminium piston. (2021) - Ravichandran, T.; Padmanabhan, S.; Daniel, S.; Kishore Kanna, S.; Lenin, Akash; Venkatesh, A.P.
Abstract: Morden material study has evolved a long way through years of scientific development and research, there are a lot of technological, industrial methods used to modify the properties of a material for the required application. One such method is called Anodization of Aluminium. The aluminium has a unique property unlike other metals, when aluminium is corroded, it forms a layer of Alumina and this substrate consists of a uniform, immobile, dense honeycomb structure. The properties of the final anodized aluminium can be modified by controlling the variables in the anodizing process. The project aims to identify the effect of Silicon on Anodization. The process is simulated in software and compared to standard Aluminium. The results show that the effect of Aluminium coated with silicon results in higher structural integrity and enhances the structural properties in aluminium.